Labels in Education: The Role of Parents and Parental Cultural Capital in Acquiring Diagnoses and Educational Accommodations - DeRoche, Christina (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
This study provides a qualitative examination of the original tenets of Labelling Theory (LT) within the realm of education using a relatively new medical label, developmental coordination disorder. Labelling Theory, although initially proposed in the areas of crime and deviance, has been applied to mental illness and educational labels. However, recent social changes have prompted a renewal of its sustainability in these areas. This study empirically evaluates the original tenets of LT and explores the role of parents in the diagnostic process. Arguably, parents play an active role in their well-being and educational opportunities today; this study uses one case in exploring this role and in asking four research questions. It finds that parents, from beginning to end, played an active role in acquiring formal labels and services for their children throughout the diagnostic process and afterwards. Parents drew from the considerable resources and capital in this process. The findings of this article have profound implications for health care policies and educational policies, which are discussed in this article.